METTL3-Mediated ADAMTS9 Suppression Facilitates Angiogenesis and Carcinogenesis in Gastric Cancer - Wang, Nuofan; Huo, Xinying; Zhang, Baoguo; Chen, Xiaoxiang; Zhao, Shuli; Shi, Xuesong; Xu, Hao; Wei, Xiaowei (Frontiers in Oncology, 2022)
The role of methyltransferase-like 3 (METTL3), which participates in catalyzing N-methyladenosine (m6A) RNA modification, in gastric cancer (GC) is unclear. Here, we found that METTL3 was overexpressed in human GC. Functionally, we verified that METTL3 promoted tumor cell proliferation and angiogenesis through a series of phenotypic experiments. Subsequently, ADAMTS9 was identified as the downstream effector of METTL3 in GC, which could be degraded by the YTHDF2-dependent pathway. Finally, the data suggested that METTL3 might facilitate GC progression through the ADAMTS9-mediated PI3K/AKT pathway. Our study unveiled the fundamental mechanisms of METTL3 in GC progression. The clinical value of METTL3 in GC deserves further exploration.